The correlation between environmental parameters and the abundance of crabs in the mangrove ecosystem of Gemuruh River, Koto XI Tarusan District, West Sumatera - Dwieke Putri Wulandari; Eni Kamal; Suparno Suparno (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2023)
Crabs are a member of the mangrove ecosystem fauna and get their food source from litter. They turn the litter into detritus and maintain ecological balance. In addition, environmental conditions in the mangrove ecosystem also play an essential role in the abundance of brachyuran crabs. Influential environmental factors include temperature, salinity, water pH, and substrate type. This study aims to determine the effect of environment types on the presence of brachyuran crabs from families Ocypodidae and Sesarmidae in the mangrove ecosystem in Gemuruh River, Koto XI Tarusan District. The method used is a descriptive method, which is a direct observation approach to crabs and environmental conditions in the mangrove ecosystem area. Collection of crab samples and environmental condition data used a purposive sampling technique. The result shows six species distributed in the area, namely Uca bellator, U. rosea, Perisesarma eumolpe, Sarmatium germaini, P. plicatum, and Sesarma curoense. The distribution of species crabs in vegetation mangroves is Rhizophora stylosa, R. apiculata, R. mucronata, Sonneratia alba, and Nypa fruticans. The environmental parameters (temperature, salinity, water pH) at each station were within the relatively good category for the growth of the Ocypodidae and Sesarmidae crab families. Based on the analysis results of the relationship between the abundance of brachyuran crabs and environmental parameters (temperature, salinity, water pH), it can be seen that there is no significant correlation between temperature, salinity, and water pH with the abundance of Ocypodidae and Sesarmidae brachyuran crabs families in the mangrove ecosystem of Gemuruh River. The factor with a dominant influence on the abundance of these crabs is the substrate type.Keywords:AbundanceKoto XI TarusanMangroveOcypodidaeSesarmidae